2017
DOI: 10.1002/acr.23252
|View full text |Cite
|
Sign up to set email alerts
|

Study of Flare Assessment in Systemic Lupus Erythematosus Based on Paper Patients

Abstract: ObjectiveTo determine the level of agreement of disease flare severity (distinguishing severe, moderate, and mild flare and persistent disease activity) in a large paper‐patient exercise involving 988 individual cases of systemic lupus erythematosus.MethodsA total of 988 individual lupus case histories were assessed by 3 individual physicians. Complete agreement about the degree of flare (or persistent disease activity) was obtained in 451 cases (46%), and these provided the reference standard for the second p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…The other comes from a study published by Pisetsky et al ( 77 ) where they introduce a principal system for categorization of SLE phenotypes; i.e., defining phenotypes of SLE in groups according to interrelated criteria to define subgroups of SLE. In fact, Pisetsky's suggestion resembles data from Isenberg et al where they upon longitudinal studies of 988 SLE patients identified different clusters of phenotypes ( 76 ). The newly suggested revision of the criteria published by Aringer et al ( 5 ) and Touma et al ( 61 ) do not help much here, as these revised criteria cement non-interrelated affections into an enigmatic disease entity!…”
Section: Systemic Lupus Erythematosus—the Syndromementioning
confidence: 57%
See 1 more Smart Citation
“…The other comes from a study published by Pisetsky et al ( 77 ) where they introduce a principal system for categorization of SLE phenotypes; i.e., defining phenotypes of SLE in groups according to interrelated criteria to define subgroups of SLE. In fact, Pisetsky's suggestion resembles data from Isenberg et al where they upon longitudinal studies of 988 SLE patients identified different clusters of phenotypes ( 76 ). The newly suggested revision of the criteria published by Aringer et al ( 5 ) and Touma et al ( 61 ) do not help much here, as these revised criteria cement non-interrelated affections into an enigmatic disease entity!…”
Section: Systemic Lupus Erythematosus—the Syndromementioning
confidence: 57%
“…A classical statement promotes SLE as a prototype complex autoimmune syndrome ( 1 , 2 , 5 , 61 , 76 , 77 ). However, this statement is standing in a certain contextual, but contrafactual paradigm hampered by one central logical problem: We do not understand an etiological origin of the classification criteria, or what the link between the current criteria are.…”
Section: Systemic Lupus Erythematosus—the Syndromementioning
confidence: 99%
“…Last, we used mean SLEDAI scores over time and not the number of flares to assess SLE activity during the followup period. Our database was not designed to identify individual reactivations of the disease; indeed, the definition of lupus flare is not uniform and the issue of capturing SLE flares accurately has not been yet solved . Given the comparable SLEDAI scores during the followup period and the results of SLE‐related damage, we believe that this limitation does not bias substantially our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…When studies stratify SLE populations, conclusions drawn from one subpopulation may differ from those drawn from another. Stratification by clinical and serological phenotypes , demography and habits is qualitative, on disease activity measures quantitative 50–57. Stratification on sex, race, socioeconomic status,58–62 access to medical care, medication choice and adherence,63 willingness to participate in clinical trials, doctor–patient interactions,64 patient preferences and perceptions,65 lifestyle choices,66 67 physician choices,68–71 environmental triggers,72–76 poverty,77 social disparities,78 and life events,79 smoking80 and the gut pathobiont81 all affect manifestations and outcomes in ways that dictate who participates in a study on SLE and in ways that cannot be examined in animal models 82.…”
Section: Stratificationmentioning
confidence: 99%
“…Payers, administrators, clinical researchers and some basic science researchers mostly select the separate illness model and the exclusive, binary and time-limited definition of SLE 115–124. Physicians, patients and other basic researchers choose the inclusive, scalar and time-variable definition and linear illness model.…”
Section: Stakeholders’ Purposesmentioning
confidence: 99%